Quality of life in a long-term care facility for the elderly in Santa Maria: an experience report (Research, Society and Development, 2020)
This research refers to an experience report of qualitative approach, elaborated in the disciplines of Scientific Writing I and Research in Psychology and Psychology of Adulthood and Old Age. It aimed to analyze the quality of life of the elderly in a rest home institution in the city of Santa Maria-RS, through the observation of interpersonal relationships, aspects related to mental health and promote an intervention according to the aspects analyzed. Data analysis was performed a posteriori using the Content Analysis method recorded in a field diary. The results of this research indicate that although the structural conditions of the asylum are satisfactory, there is still a deficit regarding psychological support to the elderly, which can bring negative points to their lives, reducing their quality of life.